Integration of Character Education and Islamic Values in the Independent Curriculum at MI Unggulan Sabilillah Lamongan - Pebrianah, Intan; Huriyah, Lilik (Jurnal Pengabdian Nusantara, 2024)
In this study, what was raised was how the morals of students and the process of fostering character building and moral values in students at MI Unggulan Sabilillah Lamongan. The purpose of this study was to determine the activities of forming moral values in students at MI Unggulan Sabilillah Lamongan. This research method uses qualitative methods with observation, interviews and documentation. The subject of this research is the Head of the madrasah and the head of the curriculum and students of MI Unggulan Sabilillah Lamongan, while the object of research is the formation of character values in MI Unggulan Sabilillah Lamongan. The results showed that the character education of students in MI Unggulan Sabilillah can be seen from the habits or traditions carried out by students. Some of the habits or traditions carried out by students in the formation of character education in the independent curriculum include: Broadly speaking, the character education material of these students is related to the character related to Allah SWT, the character related to knowledge, and the character related to other fellow humans. The activity of forming character education values at MI Unggulan Sabilillah Surabaya is carried out using the method of Islamic studies, practice and habituation, and the ibrah method.